A comparison of start techniques used in elite swimming: The stationary start versus the relay changeover - Smith, N. D. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
Traditionally, it has been assumed that the `flying start` used during relay changeovers is faster than the stationary start used during individual races, primarily due to utilisation of the stretch-shortening cycle. As a substantial proportion of the swimming start is spent underwater, differences in 15 m start time may mask any biomechanical differences exhibited on the starting block. Therefore, the aim of the present study was to examine the differences between stationary dive start and relay changeover techniques by measuring block time, time to 5 m, and time to 15 m and evaluate these parameters across an 8 week period of instructed relay practice. Time to 5 m and 15 m results were controlled for block time, to remove the anticipatory component of the relay changeover. Twenty-nine elite swimmers (12 female, 17 male) completed a stationary start and three relay changeovers at both the initial time point (T1) and after 8 weeks (T2). Significant differences in block time were observed between stationary starts and relay changeovers at both time points (p < .01) and relay changeovers from T1 to T2 (p < .01). There were no significant interactions between either start type for time to 5 m or 15 m, when controlling for sex and stroke. These findings suggest that the participants in the study were unable to use the benefit of the 'flying start` to reduce start time for the relay changeover, even after a period of instructed practice. This could be attributed to a lack of technical proficiency or deliberate practice. Further research should look to examine the perceptual and biomechanical variables that contribute to successful relay changeover performance.